PENERAPAN MEDIA POP UP BOOK UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL SISWA KELAS IV DI SDN PAKANDANGAN SANGRA BLUTO SUMENEP - Leli Lestari; Fauziah, Riski (Universitas Islam Raden Rahmat Malang, 2024)
This research has two research focuses that are the following main discussions: First, how teachers apply Pop Up Book media to thematic learning of social studies content of grade IV students at SDN Pakandangan Sangra Bluto Sumenep. Second, how are the learning outcomes in learning of Natural and social science with the application of Pop Up Book media for grade IV students at SDN Pakandangan Sangra Bluto Sumenep. This research uses a qualitative approach with a descriptive type of qualitative research. Sources of data obtained through Observation, structured interviews, and documentation. The results of this study show that: First, in the application of Pop Up Book media is very necessary to make students more enthusiastic and motivated in the learning process, because grade IV students still tend to be passive in following learning and students still do not understand the material provided by the teacher. In the application of Pop Up Book media, teachers prepare the things needed such as: rpp and media that are in accordance with learning materials of Natural and social science content (livelihoods of residents based on their place of residence). Second, that the application of Pop Up Book media can make students experience developments in improving learning outcomes in thematic learning of Natural and social science of grade IV students at SDN Pakandangan Sangra Bluto Sumenep. The improvement in student learning outcomes can be seen in the scores obtained by students after the teacher explains the material using Pop Up Book media and students are much more active in participating in learning.